SPE International Symposium on Oilfield Chemistry 2011
DOI: 10.2118/141107-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Associative Copolymer with Favorable Properties for the Application in Polymer Flooding

Abstract: A new thickener based on associative properties and its application in polymer flooding is discussed. The new thickener is an anionic, water-soluble copolymer containing pendant associative groups. These associative groups are based on a novel chemistry (patent application filed). The viscosity of the new copolymer shows superior behavior compared to existing technologies like partially hydrolyzed polyacrylamide (PHPA), especially at elevated temperature and in presence of salt respectively diva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…A proprietary hydrophobically modified sulfonated polyacrylamide (HMSPAM) (Mw = 6 × 10 6 g/mol), which contains pendant hydrophobic groups, was provided by BASF (Germany). These polymers are usually anionic‐polyacrylamide‐based tetra‐polymers with associative properties and a molar composition of hydrophobic monomer that ranges from 0.025 to 0.25 mol%, an anionic content ranging from 15 to 25 mol%, and 8 mol% of sulfonic monomer . The presence of the sulfonic monomers provides thermal stability and tolerance to high salinity…”
Section: Materials and Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…A proprietary hydrophobically modified sulfonated polyacrylamide (HMSPAM) (Mw = 6 × 10 6 g/mol), which contains pendant hydrophobic groups, was provided by BASF (Germany). These polymers are usually anionic‐polyacrylamide‐based tetra‐polymers with associative properties and a molar composition of hydrophobic monomer that ranges from 0.025 to 0.25 mol%, an anionic content ranging from 15 to 25 mol%, and 8 mol% of sulfonic monomer . The presence of the sulfonic monomers provides thermal stability and tolerance to high salinity…”
Section: Materials and Experimental Methodologymentioning
confidence: 99%
“…Hydrophobically modified polymers are currently used for polymer flooding in heavy oil reservoirs in Canada and other oil fields worldwide as has been reported . However, these polymers are still economically unfeasible for large‐scale applications because of the high manufacturing costs, the high cost of the hydrophobic monomers, and the multi‐stage chemical synthesis process . Secondly, even though hydrophobic groups are attached to the polymer backbone, the acrylamide‐based polymers still suffer more or less degradation because of mechanical shear, high salinity concentration, and susceptibility to high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the viscosity of a polymer solution is affected by various parameters at the same time in a complex way. Many researchers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] found that the viscosity of polymer solutions for EOR has a non-linear relationship with the molecular weight, degree of hydrolysis, concentration of polymer, cation concentration of polymer solution, shear rate and temperature. Considering the relatively long time required for measurement and the large number of samples induced by various influential parameters, the range of samples and the measurement conditions need to be narrow and focused.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] These factors were also proven to be responsible for the mechanical degradation. [16,21] Therefore, this study selected three different molecular-weight, partially hydrolyzed polyacrylamides to investigate their mobility reduction (apparent viscosity) and mechanical degradation during flow through a stainless steel capillary at different flow rates (shear rates). Three polymer solutions with identical viscoelastic properties (appropriate different concentrations) were forced to pass through a capillary and the influences of molecular weight and flow rate on the polymers' flow characteristics were investigated.…”
Section: Introductionmentioning
confidence: 99%